Transition Metal Complexed Crosslinked Pyrazole Functionalized Resin-Use as Polymeric Catalysts for Epoxidation of Olefins - Rathika Nath, G.; Rajesh, K. (Asian Journal of Chemistry, 2012)
Functionalized polymers are found to be highly efficient in immobilizing transition metal ions. The activity of Fe(III), Co(II), Ni(II) and Cu(II) complexes of polystyrene bound pyrazole resin have been tested towards the epoxidation of alkenes by the decomposition of hydrogen peroxide. The reactions show a first order dependence on the concentration of both the substrates and the catalyst. The metal complexes having less cross linking at the backbone and ring-activating group near the active site show high catalytic efficiency.